Influence of Biomass Based Carbon Black as Filler Composite on Tensile and Impact Strength - Nurfi Ahmadi; Fajar Nugroho (Institut Teknologi Dirgantara Adisutjipto, 2020)
Carbon blacks (CB), derived from agricultural waste, bamboo stem, coconut shells and oil palm empty fiber bunch, were obtained by pyrolysi used as filler in epoxy composites. The aim of this study was to identify the effect of biomass based carbon black on the tensile and impact strength carbon black – epoxy composite. In this research, carbon black was biomass based. The matrix was epoxy resin Bakelite EPR 174 and epoxy hardener versamid 140 while, the methodology for making the composite was hand lay-up method. The composite were made at 5, 10, 15, 20 volume percentage carbon black then the composite tested with the tensile and impact strength. The highest tensile strength was 44,65 MPa 5 volume percentage carbon black and the highest impact strength was 5.47 MPa volume percentage carbon black. While, based on the result of Scanning Electron Microscope (SEM) analysis showed there were agglomeration at the particle of carbon black, pull out, and void.